REV7: a small but mighty regulator of genome maintenance and cancer development - Maggs, Lara R.; McVey, Mitch (Frontiers in Oncology, 2025)
REV7, also known as MAD2B, MAD2L2, and FANCV, is a HORMA-domain family protein crucial to multiple genome stability pathways. REV7’s canonical role is as a member of polymerase ζ, a specialized translesion synthesis polymerase essential for DNA damage tolerance. REV7 also ensures accurate cell cycle progression and prevents premature mitotic progression by sequestering an anaphase-promoting complex/cyclosome activator. Additionally, REV7 supports genome integrity by directing double-strand break repair pathway choice as part of the recently characterized mammalian shieldin complex. Given that genome instability is a hallmark of cancer, it is unsurprising that REV7, with its numerous genome maintenance roles, is implicated in multiple malignancies, including ovarian cancer, glioma, breast cancer, malignant melanoma, and small-cell lung cancer. Moreover, high REV7 expression is associated with poor prognoses and treatment resistance in these and other cancers. Promisingly, early studies indicate that REV7 suppression enhances sensitivity to chemotherapeutics, including cisplatin. This review aims to provide a comprehensive overview of REV7’s myriad roles in genome maintenance and other functions as well as offer an updated summary of its connections to cancer and treatment resistance.